Another new Gekko species (Squamata: Gekkonidae) from southern Vietnam - Phung, Trung My; Ziegler, Thomas (Zootaxa, 2011)
We describe a new species of the gekkonid genus Gekko from southern Vietnam on the basis of three adult specimens from Cuc Dong Cape, Ninh Hoa District, Khanh Hoa Province. Gekko truongi sp. n. is distinguished from congeners by the combination of the following characters: medium-sized species with a maximum 95.9 mm SVL; supralabials 13–15; postmentals enlarged; interorbitals 45–58; dorsal tubercles absent; well developed lateral folds; scales between mental and cloaca 160–172; ventrals 35 or 36; subdigital lamellae below first toe 11–13, below fourth toe 15–17; faint basal webbing between fingers and toes; precloacal pores in males 10 or 11; postcloacal tubercles in males 1/1; number of transverse dorsal scale rows in the middle of the third caudal whorl 11; a prominent light postocular stripe is lacking; dorsum grey with dark pattern and light blotches and lines.